Exclusive, Dual, and Polytobacco Use Among US Adults by Sociodemographic Factors: Results From 3 Nationally Representative Surveys. Issue 3 (March 2021) - Hirschtick, Jana L.; Mattingly, Delvon T.; Cho, Beomyoung; Arciniega, Luis Zavala; Levy, David T.; Sanchez-Romero, Luz Maria; Jeon, Jihyoun; Land, Stephanie R.; Mistry, Ritesh; Meza, Rafael; Fleischer, Nancy L.
Purpose: To provide tobacco product use patterns for US adults by sociodemographic group. Design: A secondary analysis of Tobacco Use Supplement to the Current Population Survey (2014-15), National Health Interview Survey (2015), and Population Assessment of Tobacco and Health (2015-16). Setting: United States. Sample: Three nationally representative samples of adults (N = 28, 070-155, 067). Measures: All possible combinations of cigarette, Electronic Nicotine Delivery Systems (ENDS), other combustible product, and smokeless tobacco use, defined as current use every day or some days. Analysis: Weighted population prevalence and proportion among tobacco users of exclusive, dual, and polyuse patterns by sex, race/ethnicity, education, income, and age. Results: Exclusive cigarette use was the most prevalent pattern (10.9-12.8% of US population). Dual and polyuse were less prevalent at the population level (2.6-5.2% and 0.3-1.3%, respectively) but represented 16.7-25.5% of product use among tobacco users. Cigarette plus ENDS use was similar by sex, but men were more likely to be dual users of cigarettes plus other combustibles or smokeless tobacco. Among race/ethnic subgroups, non-Hispanic (NH) Whites were most likely to use cigarettes plus ENDS, while NH Blacks were most likely to use cigarettes plus other combustibles. Dual and polyuse were generally less common among adults with higher education, income, and age. Conclusion: Differences in product use patterns by sociodemographic group likely represent different risk profiles with important implications for resulting health disparities.